The Need For a Healthy Lifestyle in Patients With Multi Drug Resistant (MDR) Pulmonary TB in The Medical Intensive Care Unit (MICU): a Case Report - Soleha, Nisa Cahya; Anna, Anastasia; Emaliyawati, Etika (Universitas Padjadjaran, 2025)
Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. A healthy lifestyle, including adherence to Anti-Tuberculosis Drugs, quitting smoking, a balanced diet, and regular physical activity, is essential for eradicating the bacteria. This study used a case report method focusing on a 55-year-old male patient with MDR-TB and type 2 diabetes mellitus who was admitted to the Medical Intensive Care Unit. The patient presented with complaints of productive cough, fever, and fatigue. His condition worsened until death, with a history of unhealthy lifestyle habits such as smoking, poor diet, lack of physical activity, and non-adherence to Anti-Tuberculosis Drugs. The management of Multi Drug Resistant Tuberculosis requires integration between pharmacological therapy and healthy lifestyle habits. Family education and lifestyle interventions are crucial to improve medication adherence, treatment success, and the recovery process in patients with Multi Drug Resistant Tuberculosis. Adopting a healthy lifestyle can strengthen the immune system, prevent disease progression, and support the recovery of patients with Multi Drug Resistant Tuberculosis and Type 2 Diabetes Mellitus.